Incidence of concurrent systemic injuries with traumatic proptosis and its effect on outcome – 100 dogs - Whinery, Nicole; Allbaugh, Rachel A.; Sebbag, Lionel; Walton, Rebecca (Frontiers in Veterinary Science, 2024)
Objective To evaluate the incidence of concurrent systemic injuries in dogs with traumatic ocular proptosis and their effect on survival to discharge. Additionally, to evaluate for associations between the type of trauma, each presenting vital signs, minimum laboratory database findings including packed cell volume, total solids, plasma glucose and lactate concentrations, and the diagnosis of concurrent systemic injury and survival. Design Retrospective study between the years 2017 and 2022. Setting One university teaching hospital and one large, private practice. Animals One hundred dogs presenting to the hospital with a diagnosis of traumatic ocular proptosis. Measurements and main results Medical records were retrospectively reviewed; signalment, breed, sex, age, weight, date of presentation, type of trauma sustained, time from trauma to presentation, vitals on presentation, and minimum laboratory database findings including packed cell volume (PCV), total solids (TS), plasma glucose concentration, and plasma lactate concentration were recorded. A modified animal trauma triage (ATT) score was retrospectively calculated. A total of 17 dogs (17%) had concurrent systemic injury. Compared to dogs without systemic injuries, dogs with systemic injuries had a significantly lower body temperature [median 101.1F (38.3C) vs. 101.6F (38.6C); P = 0.008], significantly higher plasma glucose concentrations (125 mg/dL, 6.9 mmol/L vs. 112 mg/dL, 6.2 mmol/L; P = 0.012) and approaching statistical significance, lower PCV values (median 40 vs. 46%; P = 0.051). Conclusions Dogs presenting with traumatic ocular proptosis do present with concurrent systemic, non-ocular injuries; however, these concurrent injuries do not seem to be associated with survival to discharge.